Characterization of an isolated lactase enzyme produced by Bacillus licheniformis ALSZ2 as a potential pharmaceutical supplement for lactose intolerance - Amin, Alaa A.; Olama, Zakia A.; Ali, Safaa M. (Frontiers in Microbiology, 2023)
Introduction: A common issue that affects many different ethnicities across the world is lactose intolerance. The frequency of living for individuals who recover from this issue is improved by the following numerous medical supplements available on the market. Methods: This work focused on lactase producer isolation and statistical design (Plackett–Burman, and BOX–Behnken) to maximize the effectiveness of environmental factors. A 100 strain has been discovered from dairy product-contaminated soil, a lactase producer bacteria was selected. Plackett-Burman investigated fifteen variables. Results: The most critical variables that lead to increased lactase synthesis are glucose, peptone, and magnesium sulfate (MgSO4). The ideal process conditions for the creation of lactase yield among the stated variables were then determined using a BOX-Benken design. To establish a polynomial quadratic relationship between the three variables and lactase activity, the Box-Behnken design level was used. The EXCEL-solver nonlinear optimization technique was used to predict the best form for lactase production. To get the best performance of isolated lactase, the most suitable temperature, and PH have been detected before and after the purification process of lactase. Conclusion: This study suggests that Bacillus licheniformis is a good source for the construction of (β-Galactosidase), which is the lactase enzyme, and thus it is used as a product to help patients who suffer from lactose intolerance, which causes health problems.